A Life Worth Sustaining? Bestowed Worth and Pediatric Care - Kim, Daniel T. (The Hastings Center report, 2026)
When parents request life-sustaining treatments for children who suffer from profound neurocognitive disabilities or are at the end of life, the typical ethics advice for clinicians is to accommodate the request. It can be unclear what interests such children have, and being unable to assess those interests, a clinician will tend to honor parents’ requests to continue treatments if the associated pain can be palliated. But how is the clinician not participating in using a profoundly vulnerable child merely to satisfy parental interests? In what sense can their actions be experienced as worthwhile? These circumstances can be morally distressing for clinicians, and recent efforts to justify the practice according to a relational potential standard seem problematic. We therefore propose an alternative meaningfulness standard, which builds on a notion of bestowed worth to explain how a clinician's duty to treat in these cases can be meaningful, and why it need not entail using the child as a mere means.